Utilization of Geodiversity of Mount Gamalama Eruption Products as Geotourism Activities on The Batu Angus Geotrail, Aspiring Ternate Geopark - Abdul Kadir D Arif; Ida Bagus Oka Agastya; Reza Permadi; Rizal Marsaoly; Ida Kurnia Waliyanti (BIOSAINSTEK, 2024)
The eruption activities of Gamalama Volcano produced various volcanic materials which ultimately became a geological diversity on Ternate Island. Where the identified geodiversity consists of rock types, landscapes, beaches, hot springs and underwater geology which are very beautiful and interesting. In an effort to support the development of geotourism activities in the Aspiring Ternate geopark area, research is needed regarding the use of geological diversity, especially in the Batu Angus Geotrail, to provide an overview of how it can be utilized in geotourism activities and at the same time create opportunities for economic growth. This research uses a qualitative approach utilizing the inventory of geological diversity issued by the Geological Agency, 2017 with mapping and field observations related to geological diversity and its use in geotourism activities. The geological diversity resulting from the eruptive activity of Mount Gamalama, namely producing aa lava flow, blocky lava, spatter cone, spatter vent, lava tumuli, hornito lava, lava tube, channel lava, blocky lava flow, blocky lava smoother, accreted lava, lava walls and fracture. The geological diversity contained in the Batu Angus Geotrail is used for geotourism activities in the form of trekking activities, sport tourism activities (trail running, jogging, gymnastics, yoga), adventuring, research activities, jeep tours, Geo-Edu (field trips and excursions), art attraction stages & culture and conservation activities. Utilization of the geological diversity of eruption products from Mount Gamalama provides opportunities for local communities and regional governments to develop sustainable tourism activities in the form of geotourism.